2022
DOI: 10.3390/ijms23105842
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Features of Gaucher Disease and Gaucher Disease with Parkinsonism

Abstract: Deficient acid β-glucocerebrosidase activity due to biallelic mutations in GBA1 results in Gaucher disease (GD). Patients with this lysosomal storage disorder exhibit a wide range of associated manifestations, spanning from virtually asymptomatic adults to infants with severe neurodegeneration. While type 1 GD (GD1) is considered non-neuronopathic, a small subset of patients develop parkinsonian features. Variants in GBA1 are also an important risk factor for several common Lewy body disorders (LBDs). Neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Gaucher’s Disease patients can be classified into five types (1, 2, 3, perinatal lethal, and cardiovascular) according to substrate accumulation and neuronal affections. Type 2 and 3 patients show a degree of neurodegeneration and neuropathic manifestations that resemble clinical features of PD (reviewed in [ 66 ]). Initially, this suggested that GCase deficiency degree could be an important mechanism involved in PD.…”
Section: Gba1 Mutations and Sl Metabolism Alterations As A R...mentioning
confidence: 99%
“…Gaucher’s Disease patients can be classified into five types (1, 2, 3, perinatal lethal, and cardiovascular) according to substrate accumulation and neuronal affections. Type 2 and 3 patients show a degree of neurodegeneration and neuropathic manifestations that resemble clinical features of PD (reviewed in [ 66 ]). Initially, this suggested that GCase deficiency degree could be an important mechanism involved in PD.…”
Section: Gba1 Mutations and Sl Metabolism Alterations As A R...mentioning
confidence: 99%
“…Gaucher disease is an LSD resulting from a lysosomal defect in β-glucocerebrosidase (GCase), the enzyme responsible for the degradation of GC, leading to GC accumulation, (reviewed by Aerts et al, 2019 ). In some of the disease phenotypes this leads to neuropathological effects such as dysfunctional astrocyte activation and neuronal loss (reviewed by Furderer et al, 2022 ). One treatment strategy aims to use pharmacological chaperones (PCs) to promote correct folding of mutated enzymes and their trafficking to lysosomes, enabling trafficking of the enzyme to lysosomes and restoration of enzyme function ( Parenti, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…In specific circumstances, the distinctions between the three forms of GD may become unclear. Although GD1 is clinically non-neuronopathic, in some cases, patients develop neurological symptoms 66 . Besides, some patients exhibit an intermediate phenotype that falls between GD2 and GD3 with a survival range of 3 to 8 years 67 .…”
Section: Pathophysiologymentioning
confidence: 99%